Pengaruh Pandemi Covid-19 Dengan Budaya Literasi di Sekolah Dasar - Ema Oktavia; Diana Endah Handayani; Mei Fita Asri Untari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of the study was to determine the effect of the Covid-19 pandemic on literacy culture in grade IV SD Negeri Kalicari 01 Semarang. This type of research is qualitative research. The method used is the interview method, and the questionnaire method (questionnaire). Sources of data in this study were students and teachers of class IVB SD Negeri Kalicari 01 Semarang. The data analysis technique used is the Miles and Huberman Analysis Interactive model. The results show that the culture of reading literacy during the covid-19 pandemic in the fourth grade of SD Negeri Kalicari 01 Semarang is still running, namely through online but not running optimally, but has been included in efforts to foster a literacy culture. Although there have been efforts to familiarize and develop literacy in learning by teachers, they have not been carried out consistently. Because the teacher cannot directly monitor student literacy activities and if the 15-minute literacy culture is carried out in a zoom meeting, it is difficult to condition. Based on the results of the research and discussion, it was concluded that the COVID-19 pandemic had an influence on the literacy culture in grade IV SD Negeri Kalicari 01 Semarang.